An experimental and simulation study of novel channel designs for open-cathode high-temperature polymer electrolyte membrane fuel cells. (1st March 2016) - Thomas, Sobi; Bates, Alex; Park, Sam; Sahu, A.K.; Lee, Sang C.; Son, Byung Rak; Kim, Joo Gon; Lee, Dong-Ha
Highlights: A novel open cathode configuration with uniform temperature and flow distribution. Guidelines to select channel design in terms of power, weight and web thickness. Two different cathode design configurations without pin and with pin structure. Simulation and experiment validation of flow, pressure and temperature distribution. Abstract: A minimum balance of plant (BOP) is desired for an open-cathode high temperature polymer electrolyte membrane (HTPEM) fuel cell to ensure low parasitic losses and a compact design. The advantage of an open-cathode system is the elimination of the coolant plate and incorporation of a blower for oxidant and coolant supply, which reduces the overall size of the stack, power losses, and results in a lower system volume. In the present study, we present unique designs for an open-cathode system which offers uniform temperature distribution with a minimum temperature gradient and a uniform flow distribution through each cell. Design studies were carried out to increase power density. An experimental and simulation approach was carried out to design the novel open-cathode system. Two unique parallel serpentine flow designs were developed to yield a low pressure drop and uniform flow distribution, one without pins and another with pins. A five-cell stack was fabricated in the lab based on the new design. Performance and flow distribution studies revealed better performance, uniform flow distribution, and a reduced temperature gradient across the stack; improving overall system efficiency.